2005
DOI: 10.1162/0898929053124866
|View full text |Cite
|
Sign up to set email alerts
|

Preattentive Binding of Auditory and Visual Stimulus Features

Abstract: We investigated the role of attention in feature binding in the auditory and the visual modality. One auditory and one visual experiment used the mismatch negativity (MMN and vMMN, respectively) event-related potential to index the memory representations created from stimulus sequences, which were either task-relevant and, therefore, attended or task-irrelevant and ignored. In the latter case, the primary task was a continuous demanding within-modality task. The test sequences were composed of two frequently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
95
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 68 publications
17
95
2
Order By: Relevance
“…However, the memory-based interpretation of change-related positivity must be treated with caution at least for two reasons. First, several studies reported that memory-based change detection in the visual modality was reflected by a posterior negativity (i.e., visual MMN) (e.g., Czigler et al, 2002;Heslenfeld, 2003;Winkler et al, 2005). Although the change-related positivity and the visual MMN have a similar latency and scalp-distribution, further study is necessary to systematize the relationship of the two components with inversed polarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the memory-based interpretation of change-related positivity must be treated with caution at least for two reasons. First, several studies reported that memory-based change detection in the visual modality was reflected by a posterior negativity (i.e., visual MMN) (e.g., Czigler et al, 2002;Heslenfeld, 2003;Winkler et al, 2005). Although the change-related positivity and the visual MMN have a similar latency and scalp-distribution, further study is necessary to systematize the relationship of the two components with inversed polarity.…”
Section: Discussionmentioning
confidence: 99%
“…Visual MMN at around 100-300 ms can be elicited by the infrequent deviant stimuli presented at unattended locations, which suggests the existence of pre-attentive change detection in the visual modality (e.g., Alho et al, 1992;Czigler et al, 2002Czigler et al, , 2004Heslenfeld, 2003;Kenemans et al, 2003;Lorenzo-Lopez et al, 2004;Mazza et al, 2005;Pazo-Alvarez et al, 2004;Stagg et al, 2004;Winkler et al, 2005). For the functional significance of visual MMN, however, two contrasting hypotheses have been proposed: memory-based comparison hypothesis and different refractoriness state hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, focused attention in and of itself does not affect MMN elicitation (Sussman et al, 2003b). Additionally, Sussman et al (2005a) found no significant difference in the amplitude of the MMN elicited in conditions of highly focused attention to a visual task compared to a low load visual task (watching a video) (see also Winkler et al, 2005). Thirdly, Näätänen and his coworkers established that the process generating the MMN component is based on an auditory sensorymemory representation of the standard and not by differences in the refractory state of the neural elements activated by the standard and the deviant stimuli (Näätänen, 1992;Näätänen and Alho, 1997;Näätänen and Winkler, 1999); see also Jacobsen et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…The model of the MMN results showed that the integration of sound elements with a set of sound that occur after sound segregation in independent courses, and suggests that the auditory aspect is quickly organized in distinctive courses and the integration of sequential elements for perceptual units is carried out in distinctive pre-formed courses and provides some flexibility to identify changes in sound models in the appreciation of music or speech understanding. Winkler et al (2005) 29 studied the role of attention in the auditory and visual modes. They used MMN and vMMN potentials, respectively.…”
Section: Mismatch Negativity (Mmn)mentioning
confidence: 99%